2020
DOI: 10.1088/1742-6596/1460/1/012029
|View full text |Cite
|
Sign up to set email alerts
|

Students’ mathematics problem-solving skills through the application of Problem-Based Learning model

Abstract: Education aims to foster a variety of potential which exists in human, including the potential to solve any problems, involving solving mathematical problems. This study aimed to describe students’ problem-solving skills during mathematics learning about social arithmetic through Problem-Based Learning (PBL) model. The subjects of this research were 32 Year 7 students in Banda Aceh. This study used a qualitative descriptive approach. Data collection was conducted by problem-solving skills test and interview. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…According to the findings of the interviews, teachers have trained students in problem-solving skills in chemistry study by implementing the PBL model. This model is a designed learning model which can help student improve their capacity for problem-solving (Suryani et al, 2020;Valdez & Bungihan, 2019). However, in this preliminary study, it was found that the mastery of these skills was still low, namely the dominant ones were in the poor and very poor categories with a percentage of 67.93%.…”
Section: Discussionmentioning
confidence: 76%
“…According to the findings of the interviews, teachers have trained students in problem-solving skills in chemistry study by implementing the PBL model. This model is a designed learning model which can help student improve their capacity for problem-solving (Suryani et al, 2020;Valdez & Bungihan, 2019). However, in this preliminary study, it was found that the mastery of these skills was still low, namely the dominant ones were in the poor and very poor categories with a percentage of 67.93%.…”
Section: Discussionmentioning
confidence: 76%
“…The National Council of Teachers of Mathematics (NCTM) (2000) refers to mathematical problem solving as mathematical tasks designed to provide intellectual challenges for strengthening students' math understanding. There has been growing agreement among math educators that teaching mathematics through problem solving fosters students' learning because it provides opportunities for students to play a very active role in their mathematics learning by exploring real life situations and developing their own strategies to come up with solutions (Suryani et al, 2020;Cai, 2003Cai, , 2010Hiebert et al, 2002;Lesh & Doerr, 2013;Lester, 2013;Schoenfeld, 1994). Such research has revealed that problem-solving approaches enhance the development of the logical thinking aspects of mathematics and contribute to its practical use (Resnick, 1987).…”
Section: Teaching Mathematics Through Problem Solving To Foster Stude...mentioning
confidence: 99%
“…Research Objective Research Results (Suryani et al, 2020) Indicates students' PSS about social arithmetic through models PBL.…”
Section: Table 2 Relevant Research Authormentioning
confidence: 99%